The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.1111/jocd.13540
|View full text |Cite
|
Sign up to set email alerts
|

Usefulness of home‐use microneedle devices in the treatment of pattern hair loss

Abstract: Background Microneedle devices have been used to reduce scarring and wrinkling as well as for the treatment of pattern hair loss. Aims Here, we investigated the efficacy and safety of a newly developed home‐use microneedle device for the treatment of pattern hair loss. Methods Twenty‐nine patients were assigned into three groups based on block randomization: home‐use microneedle device only, a combination of home‐use microneedle device and 5% minoxidil solution and 5% minoxidil topical solution only. Each trea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(24 citation statements)
references
References 21 publications
0
23
0
1
Order By: Relevance
“…The quantitative analyses were performed using the data extracted from 9 controlled trials. 28,[34][35][36][37][38][39][40][41] The characteristics of the 9 studies are included in Table 2. 28,[34][35][36][37][38][39][40][41] For each of the nine trials, within-study risk of bias (RoB) was assessed using Cochrane Collaboration's RoB tool.…”
Section: Clinic Al Trial S S Tudying MI Croneedling For Ag a : E Viden Ce Synthe S E Smentioning
confidence: 99%
See 1 more Smart Citation
“…The quantitative analyses were performed using the data extracted from 9 controlled trials. 28,[34][35][36][37][38][39][40][41] The characteristics of the 9 studies are included in Table 2. 28,[34][35][36][37][38][39][40][41] For each of the nine trials, within-study risk of bias (RoB) was assessed using Cochrane Collaboration's RoB tool.…”
Section: Clinic Al Trial S S Tudying MI Croneedling For Ag a : E Viden Ce Synthe S E Smentioning
confidence: 99%
“…28,[34][35][36][37][38][39][40][41] The characteristics of the 9 studies are included in Table 2. 28,[34][35][36][37][38][39][40][41] For each of the nine trials, within-study risk of bias (RoB) was assessed using Cochrane Collaboration's RoB tool. 42 As per this tool, six domains are given one of three qualitative judgements: the (1) randomization procedure, (2) concealment of allocation, (3) blinding of subjects and research staff, (4) blinding of outcome evaluator, (5) level of attrition bias, and (6) level of selective reporting are the six domains that can be judged to have either "low," "unclear," or "high" RoB.…”
Section: Clinic Al Trial S S Tudying MI Croneedling For Ag a : E Viden Ce Synthe S E Smentioning
confidence: 99%
“…[ 12 ] n = 126 (46 m, 80 f); AGA Combination: PRP, 5% minoxidil, 2.50 mg finasteride (men), 200 mg spironolactone (women) Group 1: medications + PRP injections Group 2: medications + MN + topical PRP Group 3: medications MN automated pen, 2.00 mm needles, session endpoints marked as three passes followed by PRP application 6, once every month 6 months Hair counts, hair diameters, photographic evaluation Yes, in both sexes Hair density increased in group 2 versus group 1; larger effect for groups 1 and 2 versus group 3 No serious events reported Twenty-three subjects reported transient pain after PRP 2 Sohng et al. [ 13 ] n = 29 (24 m, 5 f); AGA Combination: 5% minoxidil Group 1: home-use MN Group 2: home-use MN + 5% minoxidil Group 3: 5% minoxidil MN stamp, 0.25 mm spiral needles, endpoint sessions marked as gentle tapping 20 times in target area 52, twice weekly 6 months Hair counts, self assessments No No serious events reported; mild and transient pruritus noted in one subject 2 Burns et al. [ 14 ] n = 11 (f); AGA Combination: 5% minoxidil + MN added to ongoing hair loss treatments 5% minoxidil + MN twice per month added to ongoing hair loss treatments MN automated pen, session endpoints marked as two passes across the frontal, crown, vertex, and upper-parietal scalp 6, twice every month 3 months Photographic evaluation, self assessments Yes Investigators noted that 11/11 subjects improved at least 1–1.5 Sinclair scores No serious events reported 1 Gowda et al.…”
Section: Resultsmentioning
confidence: 99%
“…Of the seven studies testing MN with 5% minoxidil, six found statistically significantly increased hair counts versus 5% minoxidil alone, and for a range of devices and needle lengths: rollers, automated pens, and fractional radiofrequency devices with depths from 0.60 to 2.50 mm [11,15,18,19,21,23,25]. However, Sohng et al tested 5% minoxidil with a 0.25 mm needling stamp twice-weekly and found no effect on hair parameters [13]. When comparing 5% minoxidil with 0.60 mm or 1.20 mm needle lengths, Faghihi et al found that 0.60 mm needle lengths led to significant hair count and diameter increases versus 5% minoxidil, whereas 1.20 mm needle lengths only saw hair count increases versus 5% minoxidil [21].…”
Section: Discussionmentioning
confidence: 99%
“…No lado onde houve a terapia combinada, o estudo refere que a densidade dos cabelos pelo tricoscópio foi significativamente aumentada em relação ao lado da monoterapia Sohng et al (28) -Amostra: 29 pacientes (sexos masculino e feminino) -Tempo de pesquisa: 6 meses -Metodologia: foram divididos em 3 grupos para uso dos procedimentos em domicílio: grupo 1 apenas minoxidil; segundo grupo uso de minoxidil e microagulhamento; terceiro grupo apenas microagulhamento…”
Section: Autor Metodologia Resultadosunclassified